PENGARUH KUALITAS PELAYANAN KESEHATAN TERHADAP WORK FULFILLMENT MELALUI MOTIVASI KERJA PEGAWAI PLN - Ratu, Raymond; Ruspitasari, Widi Dewi; Pradiani, Theresia (Smart Education, 2025)
Abstract: This study analyzes the effect of employment classification and health service quality on work fulfillment through work motivation among permanent employees at PT PLN Customer Service Implementation Unit West Flores. The research method used a quantitative approach with purposive sampling technique on 67 employees from a population of 101 permanent employees. Data were collected through questionnaires and analyzed using SEM-PLS with SmartPLS assistance. The results show that health service quality has a significant effect on work fulfillment (p=0.000; t=12.258) and work motivation (p=0.041; t=2.048). Work motivation proved to have a significant effect on work fulfillment (p=0.000; t=5.512). Conversely, employment classification did not significantly affect work fulfillment (p=0.273) or work motivation (p=0.772). The study concludes that health service quality is a dominant factor in increasing employee work fulfillment compared to employment status. Managerial implications indicate the need to improve health service quality as the main strategy to increase employee job satisfaction. Keywords: employment classification; health service quality; work fulfillment; work motivation; sem-pls Abstrak: Penelitian ini bertujuan menganalisis pengaruh klasifikasi kepegawaian dan kualitas pelayanan kesehatan terhadap work fulfillment melalui motivasi kerja pada pegawai tetap PT PLN Unit Pelaksana Pelayanan Pelanggan Flores Bagian Barat. Penelitian menggunakan pendekatan kuantitatif dengan teknik purposive sampling terhadap 67 pegawai dari populasi 101 pegawai tetap. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan SEM-PLS dengan bantuan SmartPLS. Hasil penelitian menunjukkan bahwa kualitas pelayanan kesehatan berpengaruh signifikan terhadap work fulfillment (p=0,000; t=12,258) dan motivasi kerja (p=0,041; t=2,048). Motivasi kerja terbukti berpengaruh signifikan terhadap work fulfillment (p=0,000; t=5,512). Sebaliknya, klasifikasi kepegawaian tidak berpengaruh signifikan terhadap work fulfillment (p=0,273) maupun motivasi kerja (p=0,772). Penelitian menyimpulkan bahwa kualitas pelayanan kesehatan merupakan faktor yang lebih dominan dalam meningkatkan work fulfillment pegawai dibandingkan status kepegawaian. Implikasi manajerial menunjukkan perlunya peningkatan kualitas pelayanan kesehatan karyawan sebagai strategi utama dalam meningkatkan kepuasan kerja pegawai. Kata kunci: klasifikasi kepegawaian; kualitas pelayanan kesehatan; work fulfillment; motivasi kerja; sem-pls